Production Optimization using Nodal Analysis in Redesigning SRP on Well “MEI” South Sumatera Field - Safitri, Mairani Ananda; Rian Cahya Rohmana; Dewantoro, Rochvi Agus (Journal of Earth Energy Science, Engineering, and Technology, 2025)
South Sumatera field has a Well “MEI” produced using an artificial lift system of the sucker rod pump, currently producing 100 bfpd. The main purpose of this research is to optimize the pump by redesigning it. The methods used are determining the maximum production rate using the Fetkovich IPR method, evaluating the installed pump to obtain its efficiency volumetric value, and redesigning the pump using nodal analysis by adjusting the stroke length and stroke per minute. Evaluation shows the pump efficiency volumetrics value is 53%, which means the pump is not working optimally. The well's flow rate can still be improved, so a redesign will be conducted to optimize the well production. After the redesign, with a stroke length of 54 inches and a stroke per minute of 6.8 rpm, the well's flow rate increased from 100 bfpd to 164 bfpd, and the volumetric efficiency increased by 92%. This research provides an overview of the effectiveness of redesigning SRP by adjusting stroke length and stroke per minute to improve the pump performance and production rate.